Audit Implementasi Clinical Pathway Diare Akut pada Anak Umur 0 – 18 Tahun di Rumah Sakit Palang Merah Indonesia Bogor - Ellya Mulyaningsih; Muhammad Natsir Nugroho; Anastina Tahjoo (Syntax Corporation Indonesia, 2021)
To find out multidisplin compliance in the implementation of clinical pathway in cases of acute diarrhea in children aged 0-18 years, the completeness of clinical pathway filling in accordance with the SPO is needed as a means in improving the quality of health services and accreditation at the Bogor Indonesian Red Cross Hospital. This research is designed using mixed methode that is quantitative and qualitative with sequential mixed method design. The mixed method strategy used is sequential explanatoris sequencial design (Quan - Qual mixed methods design). The sample number of 58 cinical pathways of acute diarrhea in children was integrated in the medical record, using purposive sampling techniques. Data collection using quantitative and qualitative methods with a grounded theory approach is further analyzed using SPSS 16. Then a questionnaire was compiled to see social representations. The results of the DPJP and nurse compliance study were 100%, pharmaceuticals 0% and nutritionis 53.4%, bonam prognosis 48.3%. Average l.A. in acute diarrhea 4-6 days (51.7%). The average age of respondents was 0-5 years (93.1%), male sex 60.3%, weight 1-20kg (93.1%), liquid bab anamnesis > 5x a day (44.8%), acute diarrhea diagnosis dehydration 56.9%, acute diarrhea diagnosis variant dehydration 65.5%, 40% participant questionnaire results answered yes to filling clinical pathway manual and 76% of participants answered agreeing to complete clinical pathway filling. The results of the analysis of data from the participant questionnaire obtained the effectiveness of clinical pathway is 68% this is not in accordance with the standard set at 70%. Effectiveness is not achieved because not all multidisciplinary are involved in clinical pathway fillers. This is because audits and evaluations have not been done properly. Effectiveness can be achieved when all multidisciplinary can carry out all tasks supported by facilities and infrastructure and rules or regulations made so as to achieve the target with results-oriented and process-planned